Interpretasi Bawah Permukaan Daerah Panas Bumi Marana Desa Masaingi, Kabupaten Donggala, Provinsi Sulawesi Tengah Berdasarkan Data Anomali Magnetik - Frastika, Yustiani; Dikdik Risdianto; Mochamad Nukman; Eddy Hartantyo (Politeknik Pelayaran Sulawesi Utara, 2023)
The existence of Marana geothermal manifestations of hot springs scattered in Masaingi Sub-district, Donggala District, Central Sulawesi Province, indicates geothermal prospect zone. Therefore, in order to obtain the subsurface model and to interpret the prospect zone, has been conducted an interpretation of Marana geothermal subsurface area based on magnetic anomaly data. The research uses secondary data of magnetic anomaly obtained from Centre for Geological Resources, Bandung, Indonesia. The research area is located on UTM zone system 50 which close to the magnetic equator, therefore the reduction to equator (RTE) process is applied to the IGRF corrected dan diurnal variations. The Upward Continuation is conducted to obtain a regional magnetic anomaly on 600 meters. Furthermore, 2.5-dimensional modeling on subsurface had done by the Talwani method using Software Oasis Montaj. The 2.5-dimensional modeling results show that the contrast of magnetic susceptibility value of Marana Geothermal rocks. Medium magnetic susceptibility value are metamorphic rock complex and Tinombo Alhburg Formation with values ranging from 0,69-0,8 (x10-2SI). Formation of Molasa Celebes Sarasin and Sarasin have low magnetic susceptibility with values 0,007-0,01 (x10-2SI), whereas high magnetic susceptibility value are granite and granodiorite (1,2x10-2SI). The new intrusion is found in the body of granite and granodiorite with magnetic susceptibility value 2,1 (x10-2SI). Based on the result of Marana geothermal modelling, the prospect zone (reservoir) is estimated in the West of research area which near the Masaingi hot spring. The prospect zone is estimated to be sandstone at a depth of ± 1200 metre. The heat source is the new intrusion thought to be a heat source (diorite) with a depth of> 4500 m. Clay cap is predicted to be an altered sandstone of argillitic alteration. The Masaingi hot spring is indicated to be an upflow zone just above the heat source, while the outflow zone is estimated to be in the southern of the research area.